Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12929-018-0415-7
|View full text |Cite
|
Sign up to set email alerts
|

The chondroitin sulfate moiety mediates thrombomodulin-enhanced adhesion and migration of vascular smooth muscle cells

Abstract: BackgroundThrombomodulin (TM), a transmembrane glycoprotein highly expressed in endothelial cells (ECs), is a potent anticoagulant maintaining circulation homeostasis. Under inflammatory states, TM expression is drastically reduced in ECs while vascular smooth muscle cells (VSMCs) show a robust expression of TM. The functional role of TM in VSMCs remains elusive.MethodsWe examined the role of TM in VSMCs activities in human aortic VSMCs stimulated with platelet-derived growth factor-BB (PDGF-BB). Using rat emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(68 reference statements)
2
8
0
Order By: Relevance
“…Furthermore, we found that exosite II blocking aptamers or exosite II binding heparin interfere with PAR2 cleavage by thrombin. These results are in accordance with a recently published study that links the TM glycosaminoglycan domain to immune responses [65].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found that exosite II blocking aptamers or exosite II binding heparin interfere with PAR2 cleavage by thrombin. These results are in accordance with a recently published study that links the TM glycosaminoglycan domain to immune responses [65].…”
Section: Discussionsupporting
confidence: 93%
“…PIC as a marker of fibrinolytic system activation, predicting the formation of thrombus, assisting the diagnosis of DIC, and guiding antifibrinolytic treatment [ 17 ]. The elevated level of TM indicates an impaired vascular endothelial system [ 18 , 19 ]. t-PAIC, key marker of fibrinolytic system, suggesting thrombus progression [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal human corneas there are 8 μg of CS/DS per mg dry weight with ∼40 disaccharides per chain, which decreases to ∼15 disaccharides in corneas affected by macular corneal dystrophies ( Plaas et al, 2001 ). CSPGs are important ECM components with diverse functions in tissues, such as regulating cell adhesion, cell growth, neuronal plasticity, neuronal regeneration and cell migration, and form the bulk of the majority of connective tissues ( Coulson-Thomas et al, 2008 , 2016 ; Silver et al, 2013 ; Silver and Silver, 2014 ; Smith et al, 2015 ; Gesteira et al, 2016 ; Pai et al, 2018 ; Pudełko et al, 2019 ).…”
Section: Chondroitin Sulfate Proteoglycans (Cspgs)mentioning
confidence: 99%